Therapeutic Patient Education in Children with Atopic Dermatitis: Position Paper on Objectives and Recommendations. Issue 2 (6th March 2013) - Barbarot, Sébastien; Bernier, Claire; Deleuran, Mette; De, Linda; Eichenfield, Lawrence; El Hachem, May; Gelmetti, Carlo; Gieler, Uwe; Lio, Peter; Marcoux, Danielle; Morren, Marie‐Anne; Torrelo, Antonio; et al.
Abstract Poor adherence is frequent in patients with atopic dermatitis (AD), leading to therapeutic failure. Therapeutic patient education (TPE) helps patients with chronic disease to acquire or maintain the skills they need to manage their chronic disease. After a review of the literature, a group of multispecialty physicians, nurses, psychologists, and patients worked together during two international workshops to develop common recommendations for TPE in AD. These recommendations were structured as answers to nine frequently asked questions about TPE in AD: What is TPE and what are its underlying principles? Why use TPE in the management of AD? Who should benefit from TPE in AD? How can TPE be organized for AD? What is the assessment process for TPE in AD? What is the evidence of the benefit of TPE in AD? Who are the people involved in TPE? How should TPE be funded in dermatology? What are the limits of the TPE process?